Oral and body narratives on screen and the constitution of an university extension repository that dialogues with teaching and research - Toledo, Eliana; Oliveira, Mateus Henrique; Ferreira de Oliveira, Michelle (Guará Journal, 2022)
The pandemic period (COVID-19) was overwhelming, but, an opportunity for a “new way of doing” in different social contexts. The objective of this research was to analyze the university extension initiatives promoted by an academic laboratory during the pandemic, identifying their relationships with teaching and research. The method was documentary, having as source the YouTube channel of LAPEGI - Laboratory of Research and Experiences in Gymnastics, and as a sample, the videos of university extension initiatives (from March/2020 to December/2021), with a quali-quantitative analysis. It was identified that there were 37 initiatives, 8 essentially of extension, 7 dialoguing with teaching and 22 with research. Some traditional ones were adapted to the virtual format, such as gymnastics choreographies (3), and a festival. Others, in the teaching field dialogued more with the extension, such as round tables and on-line conferences. And still others were created, such as the “Papo Reto com a Ciência” program (22 lives), linking extension to research, as well as lectures at events. It was concluded that the pandemic scena-rio was really paradoxical, interrupting some actions, adapting others and bringing innovations, including, enabling the cons-titution of a public digital laboratory repository of university ex-tension, to be encouraged in the post-pandemic scenario.